Ki-67 index of 5% could better predict the clinical prognosis of well-differentiated pancreatic neuroendocrine tumours. (27th September 2021) - Yuan, Bing; Shi, Yanfen; Li, Yuanliang; Tan, Haidong; Jiao, Peipei; Su, Wenting; Liu, Meng; Qi, Zhirong; Tan, Huangying; Luo, Jie
Abstract: Background: The pathological classification of well-differentiated pancreatic neuroendocrine tumour (pNET) is based largely upon Ki-67 index. However, current controversies abound about the classification of pNETG1/pNETG2. Patients and methods: Clinicopathological data were retrospectively analysed for 153 pNETG1/pNETG2 patients hospitalized at China-Japan Friendship Hospital. The critical values of pNETG1/pNETG2 were examined by using the area under the receiver operating characteristic curve and survival analysis was used to compare the clinical prognosis of pNETG1/G2. Results: Among them, 52.3% were males. The median age was 49 (18–81) years and the clinical types were pNETG1 ( n  = 38) and pNETG2 ( n  = 115). According to the receiver operating characteristic curve, the optimal cut-off value was 5.5% for classifying pNETG1/pNETG2. Significant differences between pNETG1 ( n  = 101) and pNETG2 ( n  = 52) existed in overall survival ( P  = 0.001) and disease-free survival ( P  = 0.013) when Ki-67 index was 5%. Yet no significant differences existed in overall survival ( P  = 0.378) or disease-free survival ( P  = 0.091) between pNETG1 and pNETG2 when Ki-67 index was 3%. Furthermore, multivariate analysis indicated that the revised pathological grade was an independent risk factor for mortality and post-operative recurrence of pNET patients ( P  = 0.003 and 0.014; hazard ratio (HR) = 4.005 and 2.553). Conclusion: Thus, differentiating pNETG1/pNETG2 with Ki-67 index (5%) is proposed as the cut-off value and a new Ki-67 index (5%) is a better predictor of pNET mortality and post-operative recurrence than Ki-67 index (3%). Abstract : A retrospective analysis of pNET clinicopathological data revealed that the new Ki-67 index (5%) is better than the Ki-67 index (3%) in predicting pNET mortality and post-operative recurrence.